ANTIMICROBIAL ACTIVITY AND CHARACTERIZATION OF SEVEN SYNTHETIC FORMAMIDINE DISULFIDE DERIVATIVES - Yakubu, Naruka Solomon (Innovare Journal of Sciences, 2016)
The amine-formamidine disulfide (FMD), a product of the oxidation of thiourea is reacted with seven different aldehydes to yield corresponding formamidine disulfide Schiff bases, each of which possesses the characteristic C=N. The synthetic compounds were characterized by infra-red (IR) spectrum, mass spectrum (MS), 13CNMR and 1HNMR. The antimicrobial activity was tested against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The least antimicrobial activity was exhibited by 3,4,5-Trimethoxy FMD Schiff base while Anisaldehyde FMD, 3-Nitro FMD, Cinnamaldehyde FMD and Vanillin FMD all show better and comparable antimicrobial activity relative to the other Schiff bases synthesized as reported.